Legal Protection For Poor People To Get Justice Through Legal Assistance - Riza, Faishol; Setyorini, Erny Herlin (Peneliti.net, 2024)
The purpose of this research is to find out the nature of the provision of legal aid for people who cannot afford it and to find out the legal protection for people who cannot afford legal aid from the perspective of justice. In this research, a normative legal research method is used, to explain and examine the issues raised, there are several approaches that need to be taken in order to conduct a comprehensive and detailed research. In this context, researchers use a statutory approach (statue approach). The legal material analysis technique used in this research is normative/prescriptive analysis technique. Based on the results of the analysis conducted, the essence of providing legal aid for the poor is integral in a fair justice system. It is not only about providing financial assistance, but also about providing equal access to the law, protecting human rights, and maintaining justice in the legal system. Ensuring that every individual has equal access to the justice system is a crucial step in maintaining a just and democratic society.